2012
DOI: 10.1681/asn.2011050503
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Sphingosine 1-Phosphate Receptor 2 Protects against Renal Ischemia-Reperfusion Injury

Abstract: Activation of the sphingosine 1-phosphate receptor 1 (S1P 1 R) protects against renal ischemia-reperfusion (IR) injury and inflammation, but the role of other members of this receptor family in modulating renal IR injury is unknown. We found that a selective S1P 2 R antagonist protected against renal IR injury in a dosedependent manner. Consistent with this observation, both S1P 2 R-deficient mice and wild-type mice treated with S1P 2 R small interfering RNA had reduced renal injury after IR. In contrast, a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 59 publications
4
36
1
Order By: Relevance
“…Besides this protective effect of macrophage S1P 3 , the authors also showed that the S1P 1 mediates a renal protection against IRI that is independent of macrophages which is in line with several previous studies [48,82]. Furthermore, it was shown that the S1P 2 agonist SID46371153 exacerbated renal IRI, whereas the S1P 2 antagonist JTE-013 protected against renal IRI [50]. In terms of mechanism, these authors showed that inhibition of S1P 2 led to Rho kinase and HIF-1α activation, SK-1 up-regulation, S1P generation and activation of S1P 1 that consequently triggered renoprotection.…”
Section: S1p In Renal Disease Modelssupporting
confidence: 85%
See 1 more Smart Citation
“…Besides this protective effect of macrophage S1P 3 , the authors also showed that the S1P 1 mediates a renal protection against IRI that is independent of macrophages which is in line with several previous studies [48,82]. Furthermore, it was shown that the S1P 2 agonist SID46371153 exacerbated renal IRI, whereas the S1P 2 antagonist JTE-013 protected against renal IRI [50]. In terms of mechanism, these authors showed that inhibition of S1P 2 led to Rho kinase and HIF-1α activation, SK-1 up-regulation, S1P generation and activation of S1P 1 that consequently triggered renoprotection.…”
Section: S1p In Renal Disease Modelssupporting
confidence: 85%
“…Additionally, overexpression of SK-1 in HK-2 cells also protected against peroxide-induced necrosis and led to enhanced heat shock protein 27 expression that was reversed by S1P 1 antagonism [49]. Finally, Park et al [50] showed that the selective S1P 2 antagonist JTE-013 induced SK-1 expression and further attenuated necrosis and apoptosis in HK-2 cells, whereas a S1P 2 agonist had the opposite effect. Indeed, the finding that a receptor antagonist in the absence of the receptor ligand has gene inducing capability is surprising at a first glance and it can presently not be excluded that JTE-013 may have additional cellular effects, e.g.…”
Section: S1p In Renal Cellsmentioning
confidence: 99%
“…These pathways relay their signals, e.g., to transcription factors such as the activator protein AP-1, or nuclear factor κB (NF-κB). Some relevant examples of S1PR influence on gene regulation include the feedback impact of S1PR2 activation on SphK1 expression, or induction of the cyclooxygenase COX-2 by S1PR3 (which can lead to free radical buildup)-both occur via AP-1 [33][34][35]. Importantly, CERS4 and CERS5 genes are also regulated by AP-1 [36].…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of glomerulonephritis (proliferation of mesangial cells, stimulation of matrix production and inflammation) may involved the SphK1/ S1P signaling system. Indeed, many studies have shown that S1P1, S1P2, and S1P3 are involved in inflammation and fibrosis in the glomerulus and proximal tubule [191][192][193] . However, so far, investigation of the specific pathophysiological contribution of each S1P receptor and SphK subtypes are not sufficiently selective and potent to yield clear-cut answers as to which of these should be targeted for treatment [194] .…”
Section: "Novel" Gpcr That Inhibit Sodium Absorption In the Distal Nementioning
confidence: 99%